PERAN GURU AQIDAH AKHLAK DALAM MEMBENTUK PERILAKU SOPAN SANTUN PESERTA DIDIK KELAS IX DI MTS MUHAMMADIYAH CERENTI - Aprili Laviana Wayan; Andrizal Andrizal; Helbi Akbar (Universitas Islam Kuantan Singingi, 2022)
The background of this research is that politeness is a problem that is highly highlighted at this time, even this is a homework for every element both in the school environment and in the community. From the problem of lack of courtesy of students to teachers, lack of respect for friends or teachers, not listening to teacher advice, bullying friends, saying dirty, there are still many students who do not say hello when entering class, there are still many students who do not want to help friends when difficulties both inside and outside the classroom. Polite behavior in language. In the first observation, it was seen that there were still many students who were not polite, in the second and third observations, students were able to recognize politeness, and had also applied it to their daily lives. This study aims to examine the role of moral aqidah teachers in shaping the polite behavior of class IX students at MTs Muhammadiyah Cerenti. This research is a qualitative research, the population of this study is all students of MTs. Muhammadiyah Cerenti, the sample in this study amounted to 28 people, namely class IX students and 1 teacher of morals, data collection was done by means of observation, interviews and documentation as well as techniques Data analysis uses Miles and Huberman's adoption which includes data reduction, data presentation and conclusions/verification Good manners in behavior, Class IX students at MTs Muhammadiyah Cerenti already have good behavior, such as: Saying hello when meeting the teacher, helping friends who are in trouble such as lending a pen when a friend doesn't have a pen, kissing hands when meeting the teacher, and bowing body as it passes the teacher. Polite behavior in dressing, Class IX students at MTs Muhammadiyah Cerenti already know how to dress neatly. This is done by the moral aqidah teacher in order to always maintain his appearance so that it becomes a reflection for students. So that there can be a balance between teachers and students results showed that the role of the Akhlak teacher in shaping the polite behavior of Class IX students at MTs Muhamaddyah Cerenti had run it quite well, the moral aqidah teacher had performed his role as: teacher as a guide, teacher as an example, teacher as an advisor, teacher as a coach, Teachers as coaches, teachers as role models, as motivators, teachers as educators, teachers as reminders, teachers as models.